Ultrasound biofeedback treatment for persisting childhood apraxia of speech - Preston, Jonathan L.; Brick, Nickole; Landi, Nicole (American Journal of Speech-language Pathology, 2013)
Purpose: The purpose of this study was to evaluate the efficacy of a treatment program that includes ultrasound biofeedback for children with persisting speech sound errors associated with childhood apraxia of speech (CAS). Method: Six children ages 9-15 years participated in a multiple baseline experiment for 18 treatment sessions during which treatment focused on producing sequences involving lingual sounds. Children were cued to modify their tongue movements using visual feedback from real-time ultrasound images. Probe data were collected before, during, and after treatment to assess word-level accuracy for treated and untreated sound sequences. As participants reached preestablished performance criteria, new sequences were introduced into treatment. Results: All participants met the performance criterion (80% accuracy for 2 consecutive sessions) on at least 2 treated sound sequences. Across the 6 participants, performance criterion was met for 23 of 31 treated sequences in an average of 5 sessions. Some participants showed no improvement in untreated sequences, whereas others showed generalization to untreated sequences that were phonetically similar to the treated sequences. Most gains were maintained 2 months after the end of treatment. The percentage of phonemes correct increased significantly from pretreatment to the 2-month follow-up. Conclusion: A treatment program including ultrasound biofeedback is a viable option for improving speech sound accuracy in children with persisting speech sound errors associated with CAS.
82 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-315-816-076-394 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Adolescent; Apraxias; Articulation; Biofeedback; Psychology; Child; Childhood apraxia of speech; Children; Cues; Efficacy; Feedback; Sensory; Follow-Up Studies; Humans; Intervention; Male; Phonetics; Speech; Speech Disorders; Speech Therapy; Speech sound disorders; Tongue; Treatment Outcome; Ultrasonic Therapy; adolescent; apraxia; article; articulation; association; child; childhood apraxia of speech; children; clinical trial; dept.cmd; echography; efficacy; follow up; human; intervention; male; methodology; pathophysiology; phonetics; physiology; psychophysiology; sensory feedback; speech; speech disorder; speech sound disorders; speech therapy; tongue; treatment outcome; ultrasound therapy

The relationship between phonological and auditory processing and brain organization in beginning readers - Pugh, Kenneth R.; Landi, Nicole; Preston, Jonathan L.; Mencl, W. Einar; Austin, Alison C.; Sibley, Daragh; Fulbright, Robert K.; Seidenberg, Mark S.; Grigorenko, Elena L.; Constable, R. Todd; Molfese, Peter; Frost, Stephen J. (Brain and Language, 2013)
We employed brain-behavior analyses to explore the relationship between performance on tasks measuring phonological awareness, pseudoword decoding, and rapid auditory processing (all predictors of reading (dis)ability) and brain organization for print and speech in beginning readers. For print-related activation, we observed a shared set of skill-correlated regions, including left hemisphere temporoparietal and occipitotemporal sites, as well as inferior frontal, visual, visual attention, and subcortical components. For speech-related activation, shared variance among reading skill measures was most prominently correlated with activation in left hemisphere inferior frontal gyrus and precuneus. Implications for brain-based models of literacy acquisition are discussed. (C) 2012 Elsevier Inc. All rights reserved.
107 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-059-178-769-726 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Awareness; Brain; Brain Mapping; Child; Child; Preschool; Decoding; FMRI; Female; Humans; Individual differences; Male; Phonological awareness; Photic Stimulation; Psychomotor Performance; Rapid auditory processing; Reading; Speech; Speech Perception; Thalamus; Visual Perception; article; attention; child; dept.cmd; female; frontal lobe; hearing; human; human experiment; inferior frontal gyrus; left hemisphere; male; neurophysiology; normal human; occipital lobe; parietal lobe; phonetics; precuneus; preschool child; printing; reading; school child; speech; task performance; temporal lobe; visual cortex; word recognition